Perspectives on Practice: A female journey in theatre-an interview with Brenda Winter-Palmer by Ali FitzGibbon - Hill, Shonagh (Irish Journal of Arts Management and Cultural Policy, 2025)
In this Perspectives on Practice interview edited by Shonagh Hill, Ali FitzGibbon speaks to Brenda Winter-Palmer about her work as a founding member of Charabanc, an all female theatre company. They discuss her later work in supporting young people and young people with disabilities in Northern Ireland theatre. It explores the challenges of being a mother and a care-giver in the arts sector and the ways this has impacted on Winter-Palmer’s career choices.